(untitled) (Communications in Computational Physics, 2010)
The coarsening kinetics of a two-phase mixture with a large diffusional mobility disparity between the two phases is studied using a variable-mobility Cahn Hilliard equation. The semi-implicit spectral numerical technique was employed, and a number of interpolation functions are considered for describing the change in diffusion mobility across the interface boundary from one phase to another. The coarsening rate of domain size was measured using both structure and pair correlation functions as well as the direct computation of particle sizes in real space for the case that the coarsening phase consists of dispersed particles. We discovered that the average size (͞R) versus time (t) follows the ͞R10/3∝t law, in contrast to the conventional LSW theory,͞R3 ∝t, and the interface-diffusion dominated two-phase coarsening, ͞R4∝t.